Como você prova #cos 3 theta = 4 cos ^ 3 theta - 3 cos theta #?

Responda:

A prova é dada abaixo.

Explicação:

#cos3theta=cos(2theta+theta)#

#=cos2thetacostheta-sin2thetasintheta#

#=(cos^2theta-sin^2theta)costheta-2sinthetacosthetasintheta#

#=cos^3theta-sin^2costheta-2sin^2thetacostheta#

#=costheta(cos^2theta-sin^2theta-2sin^2theta)#

#=costheta(cos^2theta-3sin^2theta)#

#=cos^3theta-3sin^2thetacostheta#

#=cos^3theta-3(1-cos^2theta)costheta#

#=cos^3theta-3costheta+3cos^3theta#

#=4cos^3theta-3costheta#

Deixe um coment√°rio